2022
DOI: 10.3390/s22124638
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors for Klebsiella pneumoniae with Molecularly Imprinted Polymer (MIP) Technique

Abstract: Nosocomial infection is one of the most important problems that occurs in hospitals, as it directly affects susceptible patients or patients with immune deficiency. Klebsiella pneumoniae (K. pneumoniae) is the most common cause of nosocomial infections in hospitals. K. pneumoniae can cause various diseases such as pneumonia, urinary tract infections, septicemias, and soft tissue infections, and it has also become highly resistant to antibiotics. The principal routes for the transmission of K. pneumoniae are vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…A MIP-based electrochemical biosensor was developed to measure the changes in electrical signals in different concentrations of K. pneumoniae ranging from 10 to 10 5 CFU/mL, with a high linear response . Detection of Enterococcus faecalis (G+), K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A MIP-based electrochemical biosensor was developed to measure the changes in electrical signals in different concentrations of K. pneumoniae ranging from 10 to 10 5 CFU/mL, with a high linear response . Detection of Enterococcus faecalis (G+), K.…”
Section: Resultsmentioning
confidence: 99%
“…A MIP-based electrochemical biosensor was developed to measure the changes in electrical signals in different concentrations of K. pneumoniae ranging from 10 to 10 5 CFU/mL, with a high linear response. 29 Detection of Enterococcus faecalis (G+), K. pneumoniae (G−), P. aeruginosa (G−), and Candida tropicalis was assessed in the same recognition range from 10 1 to 10 5 CFUs/mL using mastoparan-capped magnetic nanoparticles for electrochemical detection. 30 Furthermore, a study reported a portable in-flow magnetic transduction-based instrument capable of rapid and highly sensitive detection of whole-bacterial cells in complex matrices, providing a Yes/No result with 100% sensitivity and 80.8% specificity for the detection of K. pneumoniae cells in laboratory samples.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 6 studies were conducted in the United States of America ( 22 27 ), 8 studies in China ( 28 – 35 ), while 2 studies were conducted in Canada ( 36 , 37 ) and UK ( 38 , 39 ), respectively. Only 1 study was conducted in Australia ( 40 ), Italy ( 41 ), Spain ( 42 ), France ( 43 ), Switzerland ( 44 ), Thailand ( 45 ) and Turkey ( 46 ), respectively. Across these studies, a diverse array of biosensors was delineated by the authors, with a variety of samples employed for validation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the authors of the encompassed studies characterized their biosensors as: silicon-based biosensors ( 22 , 23 , 25 ); based on nanoscale film on optical fiber ( 26 ); surface plasmon resonance biosensor ( 37 ); sensitive surface-enhanced Raman scattering biosensor ( 35 ); biosensors based on colorimetric assays ( 30 , 32 ) or on new nanocomposite materials ( 43 ); binary deoxyribozyme biosensor ( 27 ); electric and electrochemical biosensors ( 24 , 38 41 , 44 46 ); electrochemical aptasensor ( 34 ); conventional multiple cross displacement amplification technique combined with nanoparticle-based lateral flow biosensor ( 29 , 31 , 33 ), ultrasensitive nanophotonic bimodal waveguide interferometer ( 42 ), and biochip systems ( 28 , 36 ). Regarding the specimens employed in biosensor development and/or validation, 9 studies worked on clinical samples (e.g., human serum and urine samples) ( 22 , 25 , 26 , 28 , 35 , 36 , 38 , 44 , 46 ), while 13 on bacterial samples ( 23 , 24 , 29 , 30 , 32 , 33 , 37 , 39 43 , 45 ). Three studies used both clinical and bacterial samples ( 27 , 31 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods tend to be expensive, require expertise, and can be time-consuming to reveal the pathogens. They are primarily utilized in laboratory settings and are not easily operated at home (Pintavirooj et al 2022). Considering the high spread and drug resistance of Klebsiella pneumoniae, it is essential to incorporate advanced technologies to effectively combat this infection.…”
Section: Introductionmentioning
confidence: 99%